A Relationship between Dietary Patterns and Dyslipidemia in Urban-dwelling Middle-Aged Korean Men: Using Korean Genome and Epidemiology Study (KoGES) - Chung, Bonghee; Sohn, Cheongmin (Clinical nutrition research, 2019)
An increase in the prevalence of dyslipidemia has been strongly associated with the mortality rate of cardiovascular disease. We conducted a cross-sectional analysis to determine the relationship between dietary patterns and dyslipidemia in adult men aged 40-64 years. A total of 5,643 subjects from the Korean Genome and Epidemiology Study (KoGES) were selected for the final analysis. We analyzed 24-hour dietary recall data. Using principal component analysis, 3 dietary patterns were identified: rice based Korean food pattern, flour based western dietary pattern, and convenience food dietary pattern. The flour based western dietary pattern was significantly and positively associated with total cholesterol, and low density lipoprotein (LDL) cholesterol (p for trend < 0.05). With regard to the rice based Korean food pattern, the group with the highest factor score had a significantly lower risk of hyper LDL cholesterolemia (odds ratio [OR], 0.802; 95% confidence interval [CI], 0.698-0.922) and high total cholesterol levels (OR, 0.868; 95% CI, 0.761-0.990) than the group with the lowest factor score. For the flour based western dietary pattern the group with the highest factor score showed a significantly high risk of hyper LDL cholesterolemia (OR, 1.189; 95% CI, 1.033-1.367; p for trend < 0.05) than the group with the lowest factor score. Our results showed that the rice based Korean food pattern protected against dyslipidemia. In contrast, the western staple pattern, which is rich in flour and processed foods, was independently associated with dyslipidemia in urban male residents of Korea.